Looking at nurses' training from a counsellor's perspective - W. Schulte (AOSIS, 1982)
The current personnel crisis in hospitals has given rise to serious reflections and numerous investigations. Service conditions, salary structures and other issues have been a pet subject of the public media for a long time. One factor is rarely mentioned although it is far more important, namely that nurses need personal support.